Government Intervention Instincts in Nepal: An Investigation Using Document Analysis - Dangal, Dil Nath; Pokhrel, Aditya (Journal of Management, 2023)
This research analyses the government intervention’s instincts in Nepal with reference to document analysis. This study used many policy documents from the Nepali government that dealt with economic intervention based on purposive sampling. Analysis of the fiscal and monetary sector policy has been done. The methodology for this research paper’s research was document analysis. The study paper’s findings revealed that the Nepali government has been concentrating on intervening with its policies but has neglected to evaluate the impact of the intervention and how well it matched its results. The Nepali government should now concentrate on evaluating its government intervention based on the demands of the economy and the accessibility of resources. This study has also filled the geographic gap left by the other studies by using the document analysis that was not previously looked at, indicating its original contribution.